Evaluation of a Non-Enzymatic Electrochemical Sensor Based on Co(OH)2-Functionalized Carbon Nanotubes for Glucose Detection - Diego Bolaños-Mendez; Lenys Fernández; Rafael Uribe; Alisson Cunalata-Castro; Gema González; Isamara Rojas; Andrés Chico-Proano; Alexis Debut; Luis Alberto Celi; Patricio Espinoza-Montero (Sensors, 2024)
This work reports on the assessment of a non-hydrolytic electrochemical sensor for glucose sensing that is developed using functionalized carbon nanotubes (fCNTs)/Co(OH)2. The morphology of the nanocomposite was investigated by scanning electron microscopy, which revealed that the CNTs interacted with Co(OH)2. This content formed a nanocomposite that improved the electrochemical characterizations of the electrode, including the electrochemical active surface area and capacitance, thus improving sensitivity to glucose. In the electrochemical characterization by cyclic voltammetry and chronoamperometry, the increase in catalytic activity by Co(OH)2 improved the stability and reproducibility of the glucose sensor without the use of enzymes, and its concentration range was between 50 and 700 μmol L−1. The sensor exhibited good linearity towards glucose with LOD value of 43.200 µmol L−1, which proved that the Co(OH)2-fCNTs composite is judicious for constructing cost effective and feasible sensor for glucose detection.